Investment incomes vs. the trade balance: Is the current account still a meaningful concept? - Konstantin Wacker (Oesterreichische Nationalbank (OeNB), 2024)
This paper documents that cross-border investment income flows are important for explaining current account balances in major economies. Those investment incomes reflect returns on cross-border asset holdings and on balance often reach magnitudes around 5% of major economies' gross domestic product. I show that several correlates of this investment income balance differ from other current account components, including the trade balance. Both components essentially exhibit a zero correlation with each other, with considerable crosscountry heterogeneity. Moreover, I show that investment incomes are more persistent than other current account components, suggesting that more time is needed for current account imbalances to adjust. The main findings of the paper call for a more differentiated perspective on the current account in academic analysis and policy. The paper finally discusses implications for macroeconomic monitoring and surveillance, needed improvements in macro-financial data, and highlights scope for further research.
Keywords: F3; F21; F45; 330; Global imbalances; current account; international investment position; balance of payments